2009
DOI: 10.1159/000189199
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Challenge with LPS Stimulates the Release of Macrophage Inflammatory Protein 1α

Abstract: Background: Bacterial infections can cause a variety of airway diseases. Toll-like receptors (TLRs) directly respond to the presence of microbes and partake in the innate immune defense. TLR4 is activated by lipopolysaccharide (LPS), and has been detected in sinonasal tissue, epithelial cells and various inflammatory cells. Macrophage inflammatory protein 1α (MIP-1α) is a chemokine released during the inflammatory process. The present study investigated the potential role and regulation of MIP-1α in LPS-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Detection of microbes by TLRs evokes an inflammatory response. We, along with several other research groups, have demonstrated functionally active TLRs in nearly all cell types implicated in the pathogenesis of asthma and allergic airway disease, including eosinophils, neutrophils, mast cells, monocytes, dendritic cells, macrophages, B-cells, T-cells, epithelial cells and smooth muscle cells [6], [7], [8], [9], [10], [11]. Accordingly, several TLRs and TLR ligands have been associated with the development of asthma [12].…”
Section: Introductionmentioning
confidence: 84%
“…Detection of microbes by TLRs evokes an inflammatory response. We, along with several other research groups, have demonstrated functionally active TLRs in nearly all cell types implicated in the pathogenesis of asthma and allergic airway disease, including eosinophils, neutrophils, mast cells, monocytes, dendritic cells, macrophages, B-cells, T-cells, epithelial cells and smooth muscle cells [6], [7], [8], [9], [10], [11]. Accordingly, several TLRs and TLR ligands have been associated with the development of asthma [12].…”
Section: Introductionmentioning
confidence: 84%
“…The anti-apoptotic downstream mechanism that occurs via TLR4 activated by DP is involved in the PKCδ/ERK/NF-κB pathway (Figure 3 and 6). Ekman et al demonstrated that LPS activates the PKCδ/p38 MAPK/NF-κB pathway via TLR4 in nasal neutrophils and Kilpatrick et al reported that TNF-α suppresses neutrophil apoptosis via the PKCδ/ERK pathway [9], [28], [29]. These reports indicate that anti-apoptotic signaling molecules associated with DP are important to anti-apoptotic signaling in response to other stimulators in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…This might partly be related to the applied doses of allergen and LPS, but also to the low number of patients examined. Along with several groups, we have shown that challenge with allergen, but not LPS, can cause local nasal symptoms [23] and that both allergen and LPS have the ability to release an array of cytokines in the nose [23,24,25,26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%